Cascade reaction triggering and photothermal AuNPs@MIL MOFs doped intraocular lens for enhanced posterior capsular opacification prevention - Yueze Hong; Qiuna Fang; Ting Bai; Peiyi Zhao; Yuemei Han; Quankui Lin (Journal of Nanobiotechnology, 2023)
Abstract Posterior capsular opacification (PCO) is the most common complication after cataract surgery. Present strategies can’t meet the clinical needs of long-term prevention. This research reports a novel intraocular lens (IOL) bulk material with high biocompatibility and synergistic therapy. Gold nanoparticles (AuNPs) doped MIL-101-NH2 metal–organic frameworks (MOFs) (AuNPs@MIL) was firstly fabricated via in situ reductions. Then the functionalized MOFs were uniformly mixed with glycidyl methacrylate (GMA) and 2-(2-ethoxyethoxy) ethyl acrylate (EA) to form the nanoparticle doped polymer (AuNPs@MIL-PGE), and which was used to fabricate IOL bulk materials. The materials’ optical and mechanical properties with different mass contents of nanoparticles are investigated. Such bulk functionalized IOL material could efficiently remove residual human lens epithelial cells (HLECs) in the capsular bag in the short term, and can prevent PCO on demand in the long run by near-infrared illumination (NIR) action. In vivo and in vitro experiments demonstrate the biosafety of the material. The AuNPs@MIL-PGE exhibits excellent photothermal effects, which could inhibit cell proliferation under NIR and doesn’t cause pathological effects on the surrounding tissues. Such functionalized IOL can not only avoid the side effects of the antiproliferative drugs but also realize the enhanced PCO prevention in clinical practice.